Meritocracy and Popular Legitimacy. - SAUNDERS, PETER (Political Quarterly)
The article explores on the questions whether Great Britain lives in a meritocratic society, and if so, can it be celebrated or deplored. The author cites that the evidence suggests contemporary Britain is broadly a meritocratic country. He also discussed the obstacles that the lower-class individuals faces in attaining their success. Moreover, the trouble with meritocracy and its fairness are discussed.